2016
DOI: 10.1016/j.surfcoat.2016.06.047
|View full text |Cite
|
Sign up to set email alerts
|

TiC crystallite formation and the role of interfacial energies on the composition during the deposition process of TiC/a:C thin films

Abstract: TiC / amorphous carbon (TiC/a:C) nanocomposite thin films were deposited from two targets by direct current (DC) magnetron sputtering system at room temperaure. The film´s composition and morphology were studied in detail by High Resolution Transmission Electron Microscopy (HRTEM), Selected Area Electron Diffraction (SAED), X-ray Photoelectron Spectroscopy (XPS) and Raman Spectroscopy. The sputtering power of carbon target (P C ) was kept at the constant 150 W, while the sputtering power of titanium target (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Obviously, the TiC crystal grains (~ 20 nm) are noticeably larger than the nanocrystalline (~ 5 nm) TiC grains embedded in the amorphous carbon matrix, which appears to have limited the growth of TiC grains in the RC-TiC coating. The microstructural difference between the two TiCx coatings is strongly dependant on the carbon content of the coating, which is also observed in other reported works[20,22] 8.…”
supporting
confidence: 85%
“…Obviously, the TiC crystal grains (~ 20 nm) are noticeably larger than the nanocrystalline (~ 5 nm) TiC grains embedded in the amorphous carbon matrix, which appears to have limited the growth of TiC grains in the RC-TiC coating. The microstructural difference between the two TiCx coatings is strongly dependant on the carbon content of the coating, which is also observed in other reported works[20,22] 8.…”
supporting
confidence: 85%
“…X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) were used to study and compare the chemical compositions and morphologies of the deposited TiC/a:C protective thin films. XPS has been used to evaluate the chemical composition of the TiC/a:C nanocomposite coatings using an Al anode similarly to our previous experiments [27,34,35] containing the detailed description of this measurement. The XPS signal was collected from a macroscopic 5 × 5 mm area.…”
Section: Methodsmentioning
confidence: 99%
“…The quantities that can be calculated from the measured intensities are 2-4% which increases with the Ti content of the layer. 32 The mechanical measurements showed that by incorporating a small amount of titanium, that is, approximately 13 at. % into a:C resulted in a softening of the films (Table 1).…”
Section: Amorphous Tic/a:c Thin Filmsmentioning
confidence: 99%